Pelaksanaan Pengaturan Hak Menguasai Negara atas Tanah Menurut UUD 1945 - Winahyu Erwiningsih (Fakultas Hukum Universitas Islam Indonesia, 2009)
This research was based on how the implementation of regulation of state’s authority rights over land according to UUD 1945. Promovenda thought that one of urgently and crucial issue was not properly cleared and strictness of UUPA to explain the definition means and substance of state’s authority rights over land that might caused misinterpretation. This research was using normative method with explanatory-analytical type. Researcher was using juridical-normative, comparative and historical approach. Qualitative method was used in data analysis. The research generated few results. First, state’s authority rights over land is an implementation of people’s rights based on right and responsibilityequality of Indonesian people which have an original characteristic that sub stain to achieve nation welfare. Second, the implementation of the State’s authority rights is not entirely showed in law regulations so the state has obstacles to execute their authority. Third, the State has no political will to executed the agrarian politic consequently recognized by doing a single interpretation of state’s authority rights over land based on the political regime interests.Key word: State’s authority rights, land